Bio-macromolecular design roadmap towards tough bioadhesives. (21st October 2022) - Montazerian, Hossein; Davoodi, Elham; Baidya, Avijit; Badv, Maryam; Haghniaz, Reihaneh; Dalili, Arash; Milani, Abbas S.; Hoorfar, Mina; Annabi, Nasim; Khademhosseini, Ali; Weiss, Paul S.
Abstract : Bioadhesive materials are promising candidates for sealing wounds as replacements for suturing and stapling techniques. Design of biomaterials involves introducing adhesive functionality into tough polymer networks. Abstract : Emerging sutureless wound-closure techniques have led to paradigm shifts in wound management. State-of-the-art biomaterials offer biocompatible and biodegradable platforms enabling high cohesion (toughness) and adhesion for rapid bleeding control as well as robust attachment of implantable devices. Tough bioadhesion stems from the synergistic contributions of cohesive and adhesive interactions. This Review provides a biomacromolecular design roadmap for the development of tough adhesive surgical sealants. We discuss a library of materials and methods to introduce toughness and adhesion to biomaterials. Intrinsically tough and elastic polymers are leveraged primarily by introducing strong but dynamic inter- and intramolecular interactions either through polymer chain design or using crosslink regulating additives. In addition, many efforts have been made to promote underwater adhesion via covalent/noncovalent bonds, or through micro/macro-interlock mechanisms at the tissue interfaces. The materials settings and functional additives for this purpose and the related characterization methods are reviewed. Measurements and reporting needs for fair comparisons of different materials and their properties are discussed. Finally, future directions and further research opportunities for developing tough bioadhesive surgical sealants are highlighted.